Death of a Platform? - Anders Olof Larsson (Journal of Quantitative Description: Digital Media)
While a series of case studies have provided useful insights into the political uses of Twitter, scholars have pointed to the necessity for longitudinal and cross-country findings in order to further our understanding of social media use in this regard. The study at hand presents a comparative analysis of Scandinavian political party communication on Twitter. Adopting a longitudinal approach, the study details the full histories of party Twitter accounts from Denmark, Norway and Sweden in order to provide overarching, structural insights into how the studied political parties have made use of Twitter – but also how their potential voters have chosen to engage with the tweets posted by the parties. While Twitter once was described as integral for political campaigning and indeed for the hybrid media systems in these countries, the results indicate an overall declining trend when it comes to use - albeit an increase of what could be considered as less demanding types of use for parties and citizens alike. Implications and opportunities for further research are discussed.